Аналіз сучасного стану ДГМ України - Тревого, І.; Ільків, Є.; Галярник, М.; Trevoho, I.; Ilkiv, Ye.; Haliarnyk, M. (Видавництво Львівської політехніки, 2019)
Purpose is to carry out an analysis of the survey results of State Geodetic Network (SGN) points on the territory of Ukraine performed by the territorial divisions of the State Service for Geodesy, Cartography and Cadastre of Ukraine. Conduct a study to determine the impact of population density and forestry in the region on the number of lost points. Perform analysis of losses of geodetic points during the period of independence of our state. Pay attention to the lack of scientific and economic substantiation of the allowable number of points losses, as well as the availability of points that are unavailable and increase their number in the future. Consider the measures for the use of inaccessible points, which is due to an increase in the importance of private ownership of land in the community. Develop proposals for the correct interpretation of the protection zone around the points by introducing into the practice of field topographic and geodetic works of various types and types of easements. Method. The methods of mathematical statistics, mathematical methods of recording and ranking, methods of system analysis and quantitative methods of “operations research” are used to process the results of the SGN points examination. Results. On the territory of Ukraine during 2017–2018 a full-scale survey of the geodesic (planned) network points status of 1, 2 and 3 classes was carried out in order to check their condition on the ground. Scientific novelty and practical significance. The performed analysis allows to assess the changes in the status of the SGN, to estimate the loss of geodetic points in the regions and in the classes of networks over the past decades, to identify new trends in the status of the geodetic network, which will give grounds for the generalization of conclusions by the department of state geodetic supervision of the topographic, geodetic and cartographic activity of the State Service for Geodesy, Cartography and Cadastre of Ukraine apparatus. Practical worth of the work is to solve the problem of ensuring the functioning, development, modernization, reconstruction of the state geodetic network during the implementation of the State target scientific and technical program for the development of topographic and geodetic activity and national mapping.
Analysis of the present status of the state geodetic network of Ukraine
Keywords: пункти ДГМ України; Держгеокадастр; знищені пункти; залісненість; густота населення; охоронна зона; сервітути; State Geodetic Network points of Ukraine; State Service for Geodesy; Cartography and Cadastre of Ukraine; destroyed points; forestry; population density; protection zone; easements; 528.4